2014
DOI: 10.1088/1748-0221/9/10/c10024
|View full text |Cite
|
Sign up to set email alerts
|

A multigap resistive plate chamber array for the Extreme Energy Events project

Abstract: The Extreme Energy Events (EEE) Project is a Centro Fermi - CERN - INFN - MIUR Collaboration Project for the study of extremely high energy cosmic rays, which exploits the Multigap Resistive Plate Chamber (MRPC) technology. The excellent time resolution and good tracking capability of this kind of detector allows us to study Extensive Air Showers (EAS) with an array of MRPC telescopes distributed across the Italian territory. Each telescope is installed in a high school, with the further goal to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The new statistics now available has opened up the possibility for new studies and has improved the quality of the preliminary results already published such as the detection of EAS [12] or the study of Forbush decreases [8,10]. In this section we will focus on a few examples of data analyses, trying to emphasize the importance of the telescope performance already discussed.…”
Section: Physics Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The new statistics now available has opened up the possibility for new studies and has improved the quality of the preliminary results already published such as the detection of EAS [12] or the study of Forbush decreases [8,10]. In this section we will focus on a few examples of data analyses, trying to emphasize the importance of the telescope performance already discussed.…”
Section: Physics Resultsmentioning
confidence: 99%
“…The dependence of the efficiency from the applied HV has been reported for example in Refs. [2,[6][7][8].…”
Section: Chamber and Telescope Performancementioning
confidence: 99%
“…Preliminary results from the Pilot Run and Run1 on main topics such as EAS detections and studies of the cosmic ray flux, have been reported in [12][13][14]16]; two studies on the anisotropies research for the low energy primaries [17], and the upward-going particles [18] have been already published.…”
Section: Recent Physics Resultsmentioning
confidence: 99%
“…The cosmic ray telescopes employed by the EEE Collaboration have been described in detail in many previous papers [16][17][18][19][20][21]. Recently, a review of the overall performance of such devices has been published [22].…”
Section: Experimental Setup 21 the Eee Mrpc Telescopesmentioning
confidence: 99%